Opposing Forces? Intergenerational Social Mobility and the Transmission of Political Ideology - van Ditmars Mathilde M. (Swiss Journal of Sociology, 2020)
This study investigates the consequences of intergenerational social mobility for the transmission of political ideology from parents to adult children, taking the parental ideology explicitly into account. Analyses using German and Swiss household data show that especially the vertically upwardly mobile are less influenced by the parental ideology. However, longitudinal analyses do not indicate causal effects, but a self-selection mechanism into social mobility. These findings have consequences for the perception of social mobility effects.